Meaning-Making, Forgiveness, and Gratitude: Nurturing a Healthy, Peaceful, and Prosperous Haiti - Ani Kalayjian (Peoples' Friendship University of Russia (RUDN University), 2020)
We have witnessed the growth and resilience of the Haitian people since 2010 and the devastating earthquake, in over fourteen humanitarian missions. In addition, MeaningfulWorld's global presence, which aims to raise consciousness and nurture resilience and sustainability among local and global communities in Haiti, has highlighted perspectives from vulnerable and marginalized groups including children, women, and traumatized refugees. The results of this work has addressed the ultimate question in resolving emotional and psychological scars and promoting meaning, healing, hope, reconciliation, and trust: what lessons have we learned from our traumatic past? For MeaningfulWorld ambassadors, the only healthy and permanent means of resolution for past traumas is through integration of emotional intelligence (EQ), spiritual connections, love, meaning-making, forgiveness, and empathy, and nurturing gratitude as a basic foundation. This paper will describe the value of cultivating gratitude as a foundation and utilizing forgiveness and meaning-making through post trauma growth, building resilience, and emotional intelligence. Although historically Haiti has shown resilience, while the lessons learned are not only unclear, it is fragmented, misguided, and focused on fear derived from mass spread of horizontal violence, where the majority of the Haitian population pull one another down, and call it the 'Haitian disease.'